Unveiling the Depths: Unravelling Stakeholder Values in the Landscape of Bangkoks Urban Waterways - Wanida Numsuk; Nicola Dempsey (My University, 2024)
The city of Bangkok is built on an elaborate network of waterways shaped by its historical settlement process, underscoring the profound bond between humans and the natural landscape. In light of Bangkok’s rapid urban transformation and its status as one of Southeast Asia’s most vulnerable coastal metropolises, this paper seeks to explore the intricacies of Bangkok’s waterway landscape by examining how stakeholders address its value. This research draws insights from qualitative data collection involving government agencies, experts, practitioners, NGOs, and residents from three distinct waterway communities. The paper identifies distinct value categories within Bangkok’s waterways, classified as diminishing, absent, and evolving values. These values reflect the complex landscape surrounding the waterways and their relationship with flood management and heritage preservation. The study underscores the limitations of the values expressed by government agencies and in policy documents while highlighting the potential contributions of other stakeholders in enhancing waterway management. This evidence emphasises the necessity of multi-stakeholder involvement and the application of values in decisions when developing urban resilient alternatives to the ‘business-as-usual’ model prevalent in Bangkok.
Keywords: Urban landscape; Water Governance and Infrastructure